Determination of Chlamydia Trachomatis and Other Bacteria Infections in Infertile Women in Mosul (College of Basic Education Research Journal, 2025)
Chlamydia trachomatis is the most common negative gram bacteria obligate intracellular bacteria that causes sexually transmitted diseases, Chlamydia trachomatis is, an obligate intracellular bacterium, that parasitizes eukaryotic cells. C. trachomatis shows a tropism for genital and conjunctival epithelia and ocular trachoma worldwide. It affects reproductive system in women and men. If infections aren’t identified and treated, they might lead to pelvic inflammatory disorders and spread to fallopian tubes, Infections of CT are 80–90% asymptomatic,  females have been found to have the greatest rates of CT infection. Present study was carried out to diagnose genital CT infection among reproductive-age women, attending Albatool Hospital from(July to September) 2022 by Immunochromatographic test rapid test (the immunochromatographic card test represents a fast and cheap method to detect Chlamydia). Out of those women, 100 were infertile against 25 . A total of 12(12%) of the cases were found positive for CT by ICT. 12 out of 100 infertile women were positive for CT and none of fertile women were positive for CT. Also, prevalence of common microorganisms in the vagina and cervical canals of infertile women was clarified. Numerous microorganisms, including Neisseria gonorrhoeae, Candida albicans, viruses, Trichomonas vaginalis, and aerobic and anaerobic bacteria, are responsible for  common other infections in female genitalia. Evaluate  finding of wet preparation and direct gram staining of the vaginal swabs in Chlamydia positive and negative cases. the association of Chlamydia infection and culture isolate has been studied.
Keywords: Chlamydiae trachomatis; ICT; Female genital infections; STD (Neisseria gonorrhoeae)